Penerapan Latihan ROM Pasif pada Lansia dengan Penyakit Stroke - Windarti Windarti; Lilik Pranata; Aprida Manurung (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
The elderly often experience a decline in physical function that can interfere with the ability to carry out daily activities. This condition is more common in the elderly who have had a stroke, which is always accompanied by a decrease in muscle strength. Inactivity of the joint over a long period of time can lead to contracture. One of the nursing interventions that can be done to prevent this condition while increasing muscle strength is  passive Range of Motion (ROM) exercises. The purpose of this case study is to apply nursing measures to the elderly with a decrease in muscle strength that is already research-based. This scientific paper uses a case study design  with passive ROM training interventions. The number of respondents in this study was three patients. The intervention was carried out for three days on each respondent, with a frequency of twice a day for 20 minutes in the Stroke Nursing Room of Charitas Hospital Palembang. The results of the application showed an increase in muscle strength based on Manual Muscle Testing (MMT) scores in all respondents. Mr. P experienced an increase in the muscle strength of the left hand and leg from 2 to 4, Mrs. L from 2 to 3 in the right hand and foot, and Mr. A from 0 to 4 in the right hand and foot. This application is expected to add information about the use of passive ROM in stroke seniors who have decreased muscle strength.